Research Progress on Polymer-based Radiative Cooling Materials - GUO Yu; FU Hui-tan; YUE Dong-yu; HUANG Ya-wei; HUANG Zheng-qiang; FENG Shi-ran; TANG tao; FU Peng-cheng (Liang you shipin ke-ji)
In the process of grain storage, the use of low-temperature grain storage technology can effectively reduce grain losses during storage and ensure grain quality, which is of great significance for maintaining a stable grain supply. Radiative cooling materials, as a new energy-free cooling technology, achieve cooling by radiating heat in the form of electromagnetic waves into outer space. This approach can address issues associated with traditional cooling methods, such as high energy consumption and high chemical oxygen demand (COD) emissions, offering a green and environmentally friendly new approach to low-temperature grain storage. This paper explained the working principle of polymer-based radiative cooling materials and systematically introduced the composition and selection criteria of polymer-based radiative cooling systems. It also categorized and summarized polymer-based radiative cooling materials according to their structural characteristics. The existing problems with different structured radiative cooling materials, as well as future research directions, were also analyzed. This provides a certain research framework for applying radiative cooling materials to grain storage facilities to achieve low-temperature grain storage.